Survey Results on Preparedness, Coordination, and Lived Experience of First Responders in Germany and Romania 2021 - Fekete, Alexander; Rufat, Samuel; Armas, Iuliana; Aslam, Atif (DIE ERDE – Journal of the Geographical Society of Berlin, 2023)
Pluvial and riverine floods affected many areas worldwide in 2021. To better prepare for future disasters, understanding the areas of emergency and the need for disaster management improvement is necessary. This study analyzes the results of several online surveys amongst professionals and voluntary helpers active in the 2021 flood operations in Germany and Romania. The main findings from 2,333 respondents are about perceptions of motivational aspects and problems experienced in flood operations. Satisfaction with several aspects is lower in Germany, especially provision of information and coordination. Coordination and cooperation with the population are the main problematic areas in Romania. Infrastructure disruptions are a problem in Romania, especially in terms of wastewater disposal, and in Germany in terms of roads and transportation to the affected areas. Preparedness of the population and cooperation challenges are reported for Romania, but less so in Germany. The differences revealed by the survey between Germany and Romania lie not only in the magnitude of the hazard event but also in the organizational structure of disaster response.